Keabsahan Bertindak Menurut Penilaian Sendiri Anggota Polisi Terhadap Pengamanan Massa Suporter Sepak Bola - Muhammad Belva Althofurrahman; Dodi Jaya Wardana (LPPM Universitas Ekasakti Padang, 2023)
The Kanjuruhan Tragedy Is the second biggest tragedy in the world, this tragedy killed 134 (one hundred and thirty-four) people, and this tragedy occurred because of the shooting of 45 shots of tear gas by the police. Security Regulation as a tool that may not enter the stadium area, while the Republic of Indonesia Police also has its own rules regarding tear gas to control the masses, the difference between these rules will be discussed in this article, regarding the legitimacy of the use of tear gas itself because in the rules there is an opacity of laws and rules that should be used in a football match, the method used in this article is a normative juridical method, namely reviewing legal aspects, principles, rules, doctrines, and others. This research contains a study of law that is conceptualized as a norm or rule that is applied to the social sphere.